2019
DOI: 10.1055/a-0854-3739
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of carbon dioxide insufflation versus air insufflation during endoscopic retrograde cholangiopancreatography in randomized controlled trials: a systematic review and meta-analysis

Abstract: Background and study aims Ambient air is the most commonly used gas for insufflation in endoscopic procedures worldwide. However, prolonged absorption of air during endoscopic examinations may cause pain and abdominal distension. Carbon dioxide insufflation (CO2i) has been increasingly used as an alternative to ambient air insufflation (AAi) in many endoscopic procedures due to its fast diffusion properties and less abdominal distention and pain. For endoscopic retrograde cholangiopancreatography (ERCP), use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Not all patients with pain after ERCP have pancreatitis. Other causes of abdominal pain after ERCP include discomfort due to air insufflation[ 42 - 44 ] and perforation.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Not all patients with pain after ERCP have pancreatitis. Other causes of abdominal pain after ERCP include discomfort due to air insufflation[ 42 - 44 ] and perforation.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…15,16 Rogers 17 conducted a small study that first reported on the benefit of using CO 2 insufflation during colonoscopy, owing to the properties of fast absorption and improvement of adverse events caused by abdominal distention; since then CO 2 has been used for a wide variety of endoscopic procedures. 14,[18][19][20] However, evidence for the use of CO 2 insufflation during colonoscopies among pediatric population remains scarce, with data largely extrapolated from adults. The main objective of this study was to conduct a systematic review and meta-analysis of randomized controlled trials (RCTs) to assess the effectiveness of CO 2 versus air insufflation in pediatric patients undergoing colonoscopy.…”
Section: Insufflation Of Carbon Dioxide Versus Air During Colonoscopymentioning
confidence: 99%
“…On the other hand, with increased accuracy of serological tests, endoscopic investigations can be avoided for patients with celiac disease ( 16 ). Despite numerous clinical trials and reviews on the use of CO 2 insufflation for endoscopy in adults ( 7 , 9 , 17 , 18 ), data concerning pediatric patients is scarce. Over the past few years, studies have evaluated the benefits of CO 2 insufflation during GI endoscopy in pediatric patients.…”
Section: Introductionmentioning
confidence: 99%